Смелая жизнь: повести - Чарская Лидия Алексеевна (2008)
Экземпляры: аб. (2008) / Инвентарный номер: 52060 / Цена: / Сис.шифр: 84(2Рос=Рус)1-4 / Авт.знак: Ч-22 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)1-44